Effective Organization of 4k Skills in Russian Language Lessons RFL (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the rapidly evolving educational landscape, the integration of 4K skills—communication, collaboration, critical thinking, and creativity—into language teaching is essential for fostering comprehensive student development. This article examines effective strategies for organizing and enhancing these skills in Russian as a Foreign Language (RFL) lessons. Through a combination of theoretical insights and practical examples, the study provides a framework for educators to effectively incorporate 4K skills into their teaching methodologies, ultimately aiming to improve language proficiency and prepare students for the demands of the 21st century.